Teaching Factory As A Model For Maintenance and Repair Learning In Vocational Motorcycle Engineering: A Systematic Review - Jihan Jannata Abdullah; Yoto Yoto; Didik Nurhadi (Didaktika: Jurnal Kependidikan, 2025)
This study systematically reviews the implementation of the Teaching Factory (TeFa) model in vocational motorcycle engineering education, with a specific focus on maintenance and repair learning. The background of the research lies in the persistent gap between theoretical instruction and practical application in vocational schools, which often leaves graduates underprepared for the demands of the labor market. The objective of this review is to synthesize empirical evidence on how TeFa supports the development of technical and soft skills, while also identifying enabling and inhibiting factors that influence its effectiveness. A Systematic Literature Review (SLR) approach was employed using the PRISMA protocol, analyzing 16 selected articles published between 2018 and 2025 from international and national journals. Data were extracted and analyzed thematically to identify recurring patterns and critical insights. The findings reveal that TeFa enhances students’ diagnostic, servicing, and repair skills, while fostering teamwork, communication, and problem-solving abilities. Supporting factors include adequate facilities, curriculum alignment, and industry partnerships, whereas challenges involve limited equipment, insufficient practice time, and teacher readiness. The study concludes that TeFa not only advances theories of work-based learning and competency-based training but also provides significant implications for policymakers, educators, and industry stakeholders.